2006
DOI: 10.1117/12.651124
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual study of the impact of varying frame rate on motion imagery interpretability

Abstract: The development of a motion imagery (MI) quality scale, akin to the National Image Interpretibility Rating Scale (NIIRS) for still imagery, would have great value to designers and users of surveillance and other MI systems. A multiphase study has adopted a perceptual approach to identifying the main MI attributes that affect interpretibility. The current perceptual study measured frame rate effects for simple motion imagery interpretation tasks of detecting and identifying a known target. By using synthetic im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Initial derivations were done by Irvine et al [48,49,50,51] to lay a foundation for a motion imagery quality metric that utilized the NIIRS ground sampling distance. They looked at the varying frame rate [52], perceived interpretability [53], and eventually the interpretability scale [54]. The methods were used for performance modeling for target recognition [55,56].…”
Section: Vniirsmentioning
confidence: 99%
“…Initial derivations were done by Irvine et al [48,49,50,51] to lay a foundation for a motion imagery quality metric that utilized the NIIRS ground sampling distance. They looked at the varying frame rate [52], perceived interpretability [53], and eventually the interpretability scale [54]. The methods were used for performance modeling for target recognition [55,56].…”
Section: Vniirsmentioning
confidence: 99%
“…The tasks included detection and recognition of objects, as might be done with still imagery, and the detection and recognition of activities, which relies on the dynamic nature of motion imagery. [9] • Frame Rate: These two evaluations assessed target detection and identification and other image exploitation tasks as a function of frame rate and contrast, using both synthetic imagery and real imagery [8,9] The key findings of these evaluations are:…”
Section: Perceptual Studies Of Motion Imagerymentioning
confidence: 99%
“…A number of factors were identified that had the potential to affect perceived interpretability of motion imagery: the motion of the targets, motion of the camera, GSD (spatial resolution), frame rate (temporal resolution), color, and scene complexity. These factors have been explored and characterized in a series of evaluations [6,7,8,9] • Motion and Complexity: This evaluation assessed the effects on perceived image quality of target motion, camera motion, scene complexity, and possible interactions among these factors [6,7]. • Motion and Color: This evaluation examined the effects of color, target motion, and their interactions on perceived image quality [7] • Criteria Satisfaction: Two evaluations assessed the ability of imagery analysts to perform various image exploitation tasks with motion imagery.…”
Section: Perceptual Studies Of Motion Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluations indicated that target motion has a significant positive effect on perceived image quality, whereas camera motion has a barely discernable effect.  Frame Rate: These evaluations assessed object detection and identification and other image exploitation tasks as a function of frame rate and contrast (Fenimore et al 2006). The study demonstrated that an analyst's ability to detect and recognize objects of interest degrades at frame rates below 15 frames per second.…”
Section: Image Interpretabilitymentioning
confidence: 99%